Land and Building Tax Revenue Model on Sub-District in Jambi City - Rizka Hasanah; Muhammad Rachmad R; Zulfanetti (International Journal of Business, Economics, and Social Development, 2026)
This study aims to formulate a model of Determinants of Land and Building Tax revenue on Sub-district in Jambi City. This research applied the descriptive method by utilizing quantitative data. Time series data from 2020 to 2024 were used, as well as cross-section data from 11 sub-district in Jambi City. Panel regression analysis was used to examine the data for analyisis method. The result simultaneously showed that variable notification letters for land and building tax (SPPT), tax compliance, tax service, tax receivables, and tax digitalization significantly take effect on amount of Land and Building Tax revenue on sub-district in Jambi City with percentage of contribution on 99.09% during the 2020–2024 period. In partially, variable tax service, tax receivables, and tax digitalization have a positive and significant effect on amount of Land and Building Tax revenue in sub-district of Jambi City. Meanwhile, variable SPPT and tax compliance have no significant effect.